Drivers Affecting Internal Audit Consulting Services: Contrasting Views from Demand-Side and Supply-Side Perspectives - MD GULAM SHAROAR HOSSAIN KHAN,; SUHAILY BINTI SHAHIMI,; NOOR ADWA BINTI SULAIMAN, (Asian Journal of Accounting Perspectives, 2024)
demand-side (external auditors and audit committees) and supply-side (chief audit executive and senior and middle-level internal auditors) perspectives on the drivers of internal auditor consulting services. Design/ Methodology/ Approach: An independent sample t-test was conducted using the SPSS to determine views on the differences between the two groups. The study collected the perceptions of 258 respondents, including 123 on the demand side (57 audit committee members and 66 external auditors) and 135 respondents on the supply side (60 heads of internal audit and 75 internal auditors). Research finding: On the demand side, there are significant differences in the perceptions of audit committee members and external auditors, except on senior management support, risk-based internal audits, and auditor skills and competencies. On the supply side, there are no significant differences between chief audit executives and internal auditors’ views, except on organisational culture and data analytics. Theoretical contribution/ Originality: This study extends internal audit research based on the resource-based view (RBV) theory, considering various influencing drivers (internal resources) from the perspectives of various stakeholders that affect internal auditors consulting services. Practitioner/ Policy implication: To improve the consulting services of the internal auditors, audit committees, external auditors, chief audit executives and internal auditors should develop an understanding of these conflicting views. Research limitation: Only listed companies in Bangladesh, which are better governed and regulated, were considered for data collection. Future research can focus on other developing countries and on unlisted companies. In addition, perceptions of other stakeholders, such as regulators and senior management, can also be taken into consideration.